Can we quantify the benefits of "super spikes" in track running? - Healey, L.; Bertschy, M.; Kipp, S.; Hoogkamer, W. (Sports Medicine, 2022)
The recent and rapid developments in track spike innovation have been followed by a wave of record-breaking times and top performances. This has led many to question what role "super spikes" play in improving running performance. To date, the specific contributions of new innovations in footwear, including lightweight, resilient, and compliant midsole foam, altered geometry, and increased longitudinal bending stiffness, to track running performance are unknown. Based on current literature, we speculate about what advantages these features provide. Importantly, the effects of super spikes will vary based on several factors including the event (e.g., 100 m vs. 10,000 m) and the characteristics of the athlete wearing them. Further confounding our understanding of super spikes is the difficulty of testing them. Unlike marathon shoes, testing track spikes comes with a unique challenge of quantifying the metabolic energy demands of middle-distance running events, which are partly anaerobic. Quantifying the exact benefits from super spikes is difficult and we may need to rely on comparison of track performances pre- and post- the introduction of super spikes.